Geometric Documentation Of Historical Churches in Cyprus Using Laser Scanner - Agapiou, Athos; Hadjimitsis, Diofantos G.; Themistocleous, Kyriacos (My University, 2010)
Laser scanners offer a sophisticated alternative to the conventional data collection methods, with very good resolution and accuracy. Cultural heritage sites such as churches are subject not only to natural ageing but also to natural accidents, inappropriate interventions and modifications and vandalism. Therefore, documentation is critical and laser scanner is an ideal tool for such application. This paper explores the effective use of laser scanner technology in three different churches in Cyprus. The laser scanner Leica ScanStation C10 was used for the geometric documentation of facades of historical churches and for frescoes of the 13th century. The data collection of these examples is briefly described as the post processing and the 3D modelling of the data. GIS uses the final geometric documented products for storing and management purposes for any future use by any engineer or archaeologists.